2019
DOI: 10.1016/j.ebiom.2019.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent effect of sPLA2-IIA induced proliferation on murine hair follicle stem cells and human epithelial cancer

Abstract: Background: Tissue stem cells (SCs) and cancer cells proliferation is regulated by many common signalling mechanisms. These mechanisms temporally balance proliferation and differentiation events during normal tissue homeostasis and repair. However, the effect of these aberrant signalling mechanisms on the ultimate fate of SCs and cancer cells remains obscure. Methods: To evaluate the functional effects of Secretory Phospholipase A 2-IIA (sPLA 2-IIA) induced abnormal signalling on normal SCs and cancer cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Lastly, considering that sPLA 2 -IIA is expressed in human skin ( 36 , 84 ), translation of our present study to human skin pathology is not so simple, since we need to think of the skin-intrinsic roles of sPLA 2 -IIA and the extrinsic effects of the intestinal sPLA 2 -IIA/microbiota axis, both of which can be variably influenced by environmental factors. Nevertheless, in the context of skin cancer, our results have raised the possibility that the elevated levels of sPLA 2 -IIA in human feces might have predictive values for the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, considering that sPLA 2 -IIA is expressed in human skin ( 36 , 84 ), translation of our present study to human skin pathology is not so simple, since we need to think of the skin-intrinsic roles of sPLA 2 -IIA and the extrinsic effects of the intestinal sPLA 2 -IIA/microbiota axis, both of which can be variably influenced by environmental factors. Nevertheless, in the context of skin cancer, our results have raised the possibility that the elevated levels of sPLA 2 -IIA in human feces might have predictive values for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal sPLA 2 -IIA expression is regulated by gut microbiota. Reportedly, skin-specific mouse sPLA 2 -IIA Tg mice (K14-Pla2g2a TGN ) showed increased skin carcinogenesis (35), and PLA2G2A knockdown in human skin squamous cell carcinoma reduced tumorigenesity (36). Beyond these skin-intrinsic actions of sPLA 2 -IIA in Tg mice and humans, however, the present finding that Pla2g2a -/mice displayed a skin phenotype was surprising, since it has been reported that sPLA 2 -IIA is expressed almost exclusively in Paneth cells in the small intestine of BALB/c mice (25,26,29).…”
Section: Jcimentioning
confidence: 99%
“…Moreover, sPLA2 enhances Toll-like receptor activity, as it can increase the intracellular uptake of poly(I:C), inducing phosphorylation of NF-κB and mitogen-activated protein kinases (MAPKs) in keratinocytes ( 38 ). Another PLA2, sPLA2-IIA, regulates the proliferation of tissue stem cells and cancer cells through common JNK/c-Jun signaling, thus contributing to tissue homeostasis and repair ( 39 ). Therefore, the mechanism underlying PLA2s’ regulation of the immune response in keratinocytes warrants further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…PLA2G2A -transgenic mice display notable skin abnormalities with hair loss and epidermal hyperplasia [ 27 ]. Using K14 -driven, skin-specific PLA2G2A -transgenic mice, Chovatiya et al [ 28 ] recently demonstrated that sPLA 2 -IIA promotes hair follicle stem cell proliferation through JNK signaling and that sPLA 2 -IIA-knockdown skin cancers xenografted into NOD-SCID mice show a concomitant reduction of tumor volume and decreased JNK signaling. Kuefner et al [ 29 ] showed that PLA2G2A -transgenic mice are protected from diet-induced obesity and become more prone to adipocyte browning with increased expression of thermogenic markers.…”
Section: The Spla 2 Familymentioning
confidence: 99%